2021
DOI: 10.1107/s2059798320016125
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the selenoprotein glutathione peroxidase 4 in its apo form and in complex with the covalently bound inhibitor ML162

Abstract: Wild-type human glutathione peroxidase 4 (GPX4) was co-expressed with SBP2 (selenocysteine insertion sequence-binding protein 2) in human HEK cells to achieve efficient production of this selenocysteine-containing enzyme on a preparative scale for structural biology. The protein was purified and crystallized, and the crystal structure of the wild-type form of GPX4 was determined at 1.0 Å resolution. The overall fold and the active site are conserved compared with previously determined crystal structures of mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…The animal GPx common ancestor would give rise to three different types of GPx. The closest to non-animal GPx, GPx04, retained its monomeric structure and catalytic capacity to reduce lipid peroxides [ 16 , 53 ]. Despite the absence of the amino acid residues responsible to bind to GSH, the presence of selenocysteine in the GPx04 contributed to the use of glutathione as a reducing agent [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The animal GPx common ancestor would give rise to three different types of GPx. The closest to non-animal GPx, GPx04, retained its monomeric structure and catalytic capacity to reduce lipid peroxides [ 16 , 53 ]. Despite the absence of the amino acid residues responsible to bind to GSH, the presence of selenocysteine in the GPx04 contributed to the use of glutathione as a reducing agent [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cluster #4 (necroptosis) and Cluster #6 (Fenton reaction) contain fewer nodes on the timeline, suggesting that this is a previous research hotspot or an emerging research direction. Therefore, future research should focus on comprehensive mechanism and clinical application, such as novel tumor therapies based on GPX4 covalent inhibitors, such as ML162 ( Moosmayer et al, 2021 ). In addition, p53-regulated ferroptosis therapy or CD8 + -mediated immunotherapy of cancer also has potential clinical value, which needs further research and mechanism elaboration ( Chu et al, 2019 ; Kang et al, 2019 ; Stockwell and Jiang, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…GPX4 can reduce hydroperoxides to block the lipoxygenase pathway to inhibit ferroptosis. Inactivating GPX4 with RSL3 ( Sui et al, 2018 ), ML162 ( Moosmayer et al, 2021 ), and ML210 ( You et al, 2021 ) could increase the production of lipid ROS, thereby inducing ferroptosis. Friedmann Angeli et al (2014) observed that GPX4 knockout contributed to renal failure in mice, but this injury could be rescued by ferrostatin-1, an agent that could decrease the level of iron to inhibit iron-dependent lipid peroxidation.…”
Section: Mechanisms Of Ferroptosismentioning
confidence: 99%